Adsorption of Copper (II) by magnesium hydroxide modified shell activated carbon - Kan Jin-tao; Tan Zheng-chang; Zhang Yu-feng (Adsorption Science & Technology)
Magnesium hydroxide modified activated carbon (Mg-HAAC) was obtained from the raw material of activated carbon of Prunus mira Koehne shell prepared by phosphoric acid chemical activation method (HAAC). And the physicochemical properties, Copper (II) adsorption capacity and mechanism between them were investigated. Results showed that the maximum loading rate of HAAC on magnesium hydroxide was up to 3.77%, and the Mg-HAAC has the highest adsorption capacity on Copper (II) of 23.88 mg/g when the concentration of magnesium chloride used during modification was 2.0 mol/L. The small photoelectron peak of Mg1 s at the binding energy of 1304.08 eV in X-ray photoelectron spectroscopy (XPS) plot, the strong diffraction peak at the ϴ value of 19°, 38°, and 51° in the X-ray diffraction (XRD) plot, and the irregular small particles on the surface of sample in the scanning electron microscope (SEM) image all indicated HAAC had been successfully modified to Mg-HAAC. pH would affect the adsorption capacity of HAAC and Mg-HAAC on Copper (II), and the maximum adsorption capacity occurred at pH value of 7.0. The specific surface area increased from 1551.3 m 2 /g of HAAC to 1617.5 m 2 /g of Mg-HAAC. Under the optimal adsorption conditions, the maximum Copper (II) adsorption capacities of HAAC and Mg-HAAC reached up to be 41.92 and 58.03 mg/g, respectively. The analysis results of adsorption isotherm model, adsorption kinetics model, and thermodynamic indicate that the adsorption of Copper (II) by both HAAC and Mg-HAAC was monolayer chemical adsorption with an exothermic spontaneous process. These indicated magnesium hydroxide modification could significantly improve the adsorption capacity of HAAC on Copper (II), and the modified Mg-HAAC could be developed and utilized as an effective adsorbent for Copper (II) containing wastewater.